Predicting the Future: Delivery Room Planning of Congenital Heart Disease Diagnosed by Fetal Echocardiography - Donofrio, Mary T. (American Journal of Perinatology, 2018)
Advances in prenatal imaging have improved the examination of the fetal cardiovascular system. Fetal echocardiography facilitates the prenatal diagnosis of congenital heart disease (CHD) and through sequential examination, allows assessment of fetal cardiac hemodynamics, predicting the evolution of anatomical and functional cardiovascular abnormalities in utero and during the transition to a postnatal circulation at delivery. This approach allows detailed diagnosis with prenatal counseling and enables planning to define perinatal management, selecting the fetuses at a risk of postnatal hemodynamic instability who are likely to require a specialized delivery plan. The prenatal diagnosis and management of critical neonatal CHD has been shown to play an important role in improving the outcome of newborns with these conditions, allowing timely stabilization of the circulation prior to cardiac intervention or surgery, thus reducing the risk of perioperative morbidity and mortality. Diagnostic protocols aimed at risk-stratifying severity and potential postnatal compromise in fetuses with CHD have been developed to identify those who may require special intervention at birth or within the first days of life. In addition, new methodologies are being studied to improve the accuracy of prediction of disease severity. Perinatal management of neonates with a prenatal diagnosis of CHD requires a close collaboration between obstetric, neonatal, and cardiology services. In this article, the management of fetuses with CHD will be discussed, along with summarizing the in utero and fetal echocardiographic findings used for risk stratification of newborns with CHD and reviewing the basic principles used for planning for neonatal resuscitation and initial transitional care of these complex newborns.
Keywords: fetal echocardiography; prenatal diagnosis; delivery management; congenital heart disease